A study of factors affecting test day records of dairy cattle : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Animal Science at Massey University - Wickham, Brian Walter (Massey University, 1972)
Dairyfarming in New Zealand is fundamentally concerned with obtaining an income from the sale of milk and milk fat produced by ones cows. A dairy farmer's income can be increased by either reducing the costs of production and/or increasing the value of milk and milk fat sold. One method by which income can be increased is the culling of low producers and selection of high producing replacements. In New Zealand Herd Improvement Associations provide three systems whereby the production of individual cows is measured monthly, bimonthly or twice yearly. In using these records for culling and selective breeding there are two main groups of influences that have to be taken into account - environmental influences and genetic influences. In selective breeding the major objective is in fact to separate the environmental and genetic influences so that the genetically "best" animals can be used to produce the next generation. Any attempt to evaluate either the genetic or environmental influences on test records must take into account the other. For example in bull selection the daughters of the bulls being compared may be of different ages and milked in different herds. The relative genetic value of the bulls can only be evaluated after the influence of age and herd, on daughter production, has been taken into account. Likewise in evaluating the influence of age on production the cows in each age class may be the daughters of different sires. Only by taking account of these genetic differences can the affect of the environmental factor be evaluated.
Keywords: Dairy farming; Dairy cattle genetics; Dairy herd testing